2008 IEEE Virtual Reality Conference 2008
DOI: 10.1109/vr.2008.4480751
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Group Dynamics in Large-Scale Collaborative Virtual Environments

Abstract: We have developed techniques called Mobile Group Dynamics (MGDs), which help groups of people to work together while they travel around large-scale virtual environments. MGDs explicitly showed the groups that people had formed themselves into, and helped people move around together and communicate over extended distances. The techniques were evaluated in the context of an urban planning application, by providing one batch of participants with MGDs and another with an interface based on conventional collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Previous research showed how even a basic set of MGDs techniques helped users communicate while they traveled around a virtual urban development and reviewed its design [4]. However, two major areas for improvement were also identified.…”
Section: Methods For Real-time Collaborationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research showed how even a basic set of MGDs techniques helped users communicate while they traveled around a virtual urban development and reviewed its design [4]. However, two major areas for improvement were also identified.…”
Section: Methods For Real-time Collaborationmentioning
confidence: 99%
“…Participants used two adjacent computers, one for the CVE and the other for the urban planning report write-up. The CVE application, environment and experimental procedure were the same as in [4].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations